#TITLE_ALTERNATIVE# - REZA (NIM 12205049); Pembimbing: Dr.Ir. Leksono Mucharam, FAHRAN
Field Z has three region separated by two fault that has homogenous fluid characteristic. There are four production wells. Oil produced from all the wells will be transported to the gathering station. The problem that often happen in pipe network design is the obstacle along the liquid flow because the pipeline network isn't good. The aim of my final project is to analyze the cause of the flowing obastacle in the pipe network by optimizing flow index value. The flow index can be optimized by widening the diameter of the pipes. In addition, we must also considerate the formation pipe diameter from upstream to downstream liquid flow. The better pipeline network design, the wider pipeline diameter from upstream to downstream which can reduce the flow obstacle along the pipeline especially at the branch of the pipeline. Pipeline network design is not only focus in the amount of oil produced but also investment that will be expended. So, the author will conduct economic analysis in the pipeline network design.